Chemokines in ischemia and reperfusion - Frangogiannis, Nikolaos G (Thrombosis and haemostasis, 2007)
Chemokine signaling plays an important role in the postischemic inflammatory response. Overlapping pathways involving reactive oxygen intermediates, Toll-like receptor (TLR) activation, the complement cascade and the nuclear factor (NF)-kappaB system induce both CXC and CC chemokines in ischemic tissues. Reperfusion accentuates chemokine expression promoting an intense inflammatory reaction. ELR-containing CXC chemokines regulate neutrophil infiltration in the ischemic area, whereas CXCR3 ligands may mediate recruitment of Th1 cells. CC chemokines, on the other hand, induce mononuclear cell infiltration and macrophage activation. Evidence suggests that chemokine signaling mediates actions beyond leukocyte chemotaxis and activation, regulating angiogenesis and fibrous tissue deposition. Effective repair of ischemic tissue is dependent on a well-orchestrated cellular response and on timely induction and suppression of chemokines in a locally restricted manner. This manuscript reviews the evidence suggesting a role for chemokine-mediated effects in ischemia/reperfusion and discusses the potential significance of these interactions in injury and repair of ischemic tissues.